Talent Retention at Commercial Banks in Vietnam - Mai, Nguyen Ngoc; Thuy, Vo Hoang Ngoc (International Review of Management and Marketing, 2021)
This study aims to identify talent criteria at commercial banks in Vietnam and build a scale of factors affecting talent retention. By qualitative research method through expert interviews and non-parametric testing to determine the relationship between factors affecting talent retention at commercial banks in Vietnam. The research has identified the following four factors influencing talent retention: Job satisfaction, Motivation, Commitment and Loyalty. In addition, the study surveyed the Snowball sampling method and collected 877 satisfactory questionnaires, performed quantitative research and tested the linear structural model of SEM. Research results show that among the factors that affect talent retention, job satisfaction is the most influential, followed by commitment, loyalty and work motivation. The research's contribution helps bank leaders to have appropriate policies to retain their bank's talents. Keywords: Talent retention talent, Commitment; Job satisfaction; Loyalty; Motivation. JEL Classifications: J20, J28 DOI: https://doi.org/10.32479/irmm.10908